Extent of Differentiated Gene Expression in the Human Endothelium-Derived EA.hy926 Cell Line - Rieber, Alison J; Marr, Henry S; Comer, Mary B; Edgell, Cora-Jean S (Thrombosis and Haemostasis, 1993)
Vascular endothelial cells perform many differentiated functions in processes such as angiogenesis, hemostasis, and inflammation. The number of recognized differentiated functions has increased rapidly in recent years, but there may be many more still unrecognized. The purpose of this study is to estimate the fraction of differentially expressed mRNA in a continuous human endothelium-derived cell line, EA.hy926. Random cDNA clones representing mRNAs from this cell line were labeled and used to probe blots of RNA from EA.hy926 cells and from cells of a relatively undifferentiated line. Of 49 random cDNAs, 5 cDNAs or 10% were found to represent mRNAs that are differentially expressed in EA.hy926 and in early passage umbilical vein endothelial cells. Since more than 104 different genes are thought to be expressed in the typical mammalian cell, our data indicate that about 103 gene products contribute to the differentiated properties of endothelial cells.